Development of Animated Learning Videos to Strengthen Elementary School Students' Mathematical Literacy Skills - Firdayanti Ayu Lestari; Irwan Akib; Sitti Fithriani Saleh (PT ARRUS Intelektual Indonesia, 2026)
The low mathematical literacy skills of students encourage the need for learning innovations that can improve this condition. Learning media are needed that can support the strengthening of students' mathematical literacy skills. The purpose of this study is to develop animated learning videos that are valid, practical, and effective in improving students' mathematical literacy in elementary schools. This research is a development research using the 4D model which includes the Define, Design, Develop, and Disseminate stages . The trial subjects in this study were fifth grade elementary school students. The research instruments were expert validation sheets, teacher and student activity observation sheets, teacher and student response questionnaires, and mathematical literacy tests. Data analysis was carried out descriptively quantitatively and qualitatively. The developed animated video was validated by the validator from the media and material aspects. The average score of the validator's assessment for the media aspect was 3.56 with a percentage of 89.06% and a very valid category. The average score of the validator's assessment for the material aspect was 3.81 with a percentage of 95.29% and a very valid category. In the practicality test, teachers rated the learning video with an average score of 3.58 or a percentage of 89.56%, and a very practical category, while students rated it with an average score of 3.04 or a percentage of 76.08%, and a practical category. The results of the implementation of animated learning videos in three different classes showed an N-Gain value of 0.72 or a high category, a learning implementation score of 3.87 or a very good category, a student learning activity score of 3.65 or a very active category, and a student response score of 3.23 . or very positive category . Thus, it can be concluded that the developed animated learning video is valid, practical, and effective in improving the mathematical literacy skills of fifth-grade elementary school students.